In the prime of life: ERP evidence for syntactic comprehension priming in older adults - van Boxtel, Willem S.; Lawyer, Laurel A. (Journal of Language and Aging Research, 2023)
Background: Recent studies suggest older adults’ implicit learning of syntactic patterns remains largely intact. Syntactic priming has proven to be a sensitive tool to examine this implicit sensitivity. However, most priming studies with older adults have focused on production, and none have included an electrophysiological component. This study explores the neural correlates of syntactic priming in older adults’ comprehension. Method: We used a self-paced reading and event-related potential paradigm with groups of older and younger adults. Reduced Relative targets were primed, unprimed, or lexically boosted, while reading times and EEG recordings were obtained. Pre-tests of Working Memory and Processing Speed were also recorded. Results: Older adults showed intact priming and lexical boost on reading times, while lexical facilitation was dependent on syntactic overlap in the older but not the younger group. Syntactic priming was evident on N400 and P600 modulations on verbs and nouns in Reduced Relatives, and generally did not differ by age group. This suggests older and younger adults are equally susceptible to syntactic facilitation, and makes the case for more non-declarative, electrophysiological measurements of older adults’ sentence processing ability in future studies.